A versatile strategy to synthesize N-methyl-anthranilic acid-labelled glycoprobes for fluorescence-based screening assays. Issue 73 (13th August 2020) - Bertin-Jung, Isabelle; Robert, Anne; Ramalanjaona, Nick; Gulberti, Sandrine; Bui, Catherine; Vincourt, Jean-Baptiste; Ouzzine, Mohamed; Jacquinet, Jean-Claude; Lopin-Bon, Chrystel; Fournel-Gigleux, Sylvie
Abstract : Here we propose a general strategy to label carbohydrates with N-methyl-anthranilic acid to generate glycotools for fluorescence-based screening and carbohydrate–protein interaction studies. Abstract : Here we propose a general strategy to label carbohydrates with N -methyl-anthranilic acid at the anomeric position. Through two examples, we demonstrate that the generated glycoprobes are suitable for fluorescence-based binding/competition assays. Our approach is expected to readily generate series of glycoprobes dedicated to screening assays for the discovery of drugs targeting carbohydrate–protein interactions.